(untitled) (Health Renaissance, 2017)
Background: This retrospective review was performed to identify the incidence, causes, and details of hand injuries in patients presenting to a tertiary hospital in Eastern Nepal. Objective: To identify the incidence, causes, and details of hand injuries in patients. Method: Records of all patients who had sustained hand injuries for last 5 years were collected from the medical record section. Altogether 832 injuries of hand in 484 patients were reported in this review. These patients were reviewed for age at the time of injury, gender, location of the incident, mechanism of injury, and fracture specifies. Result: 414 (85.5%) males with mean age of 28.79 ± 12.81 and in female with 30.43 ±17.13 yrs were found. Machinery injuries (25.2%) were the most common causes of injuries followed by RTA (14.5%). Metacarpal bone fractures (34.6%) were the commonest injury of the hand. Most of the patients were treated with open reduction and fixation with K wires. Conclusion: The study reveals the aetio-epidemiological and clinical aspect of hand injuries with its alarming burden in Nepal. Health Renaissance 2015;13(2): 125-133